Isokinetic muscle strength for ankle extensors and flexors: a comparison between elite sprint runners and swimmers - Özçaldiran, B.; Durmaz, B. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to evaluate through isokinetic tests the muscular condition of ankles of elite sprint swimmers and elite sprint runners, and make comparisons within these groups. Methods. Fourteen elite swimmers and 8 elite runners were included in this cross-sectional study. The ankle extensors and flexors strength characteristics of elite sprinter athletes were tested at a slow (30°/s) and a fast (120°/s) speed using an isokinetic dynamometer. Subjects were assessed by one examiner on six seperate days, within a 2-week period. Results. A significant difference was noted between right and left sides for ankle joint flexors in runners at slow speed. Runners had higher left ankle flexion measures at 30°/s and 120°/s angular velocity than swimmers. There was no significant difference between the peak torques of the left and right sides at all angular velocities in swimmers. Conclusion. To our knowledge, this is the first study to assess the ankle flexors and extensors strength characteristics of elite sprinter swimmers making a comparison with elite sprinter runners. The findings presented in this study report the sport specific difference between the sprint swimmers and sprint runners. These values add a quantative dimension to rehabilitative and preventive sports medicine for elite sprinter runners and swimmers.